Living in Scroll Land - Laura Glitsos (M/C Journal, 2025)
The experience of contemporary living is wrapped up in the practice of the ‘endless scroll.’ For subjects embedded in the sophisticated infrastructures of developed nations, there is a sense that one’s smartphone is simultaneously emancipatory technology, connective tissue, and a gothic vortex of ‘slop and doom’. In mainstream discussions, this sentiment is often articulated as feelings of being sucked into the maelstrom of “doomscrolling” (Mitchell; monstr2me) or of being drowned in digital excess, such as in discussions of consuming mindless “AI slop” (Adami). AI slop, or just ‘slop’, is low-quality, highly generic content generated by AI. This kind of content can range from bland-sounding articles to nonsensical images to repetitive videos or product reviews, designed primarily to attract engagement, also known as clickbait. This content is cheap and flooding the Internet in massive volumes, and has been likened to “unappetizing food being shovelled into troughs for livestock” that “acts as fodder for websites whose only purpose appears to be optimising for SEO as cheaply as possible” (Adami). Doomscrolling can most simply be understood as the “indiscriminate consumption” of negativity, that researchers have suggested “evokes existential anxiety and fosters pessimism about human nature” (Shabahang et al. 1). This article offers a discussion on what it feels like to live increasingly under the spectre of slop and doom; a kind of liminal ‘Scroll Land’ whereby experience is shaped by gothic undertones such as surreality, paranoia, suspicion, menace, and most of all, anxiety. In academic terms, Dag Øivind Madsen and Richard W. Puyt have recently described the phenomenon of slop in an opinion piece in the scholarly journal AI and Society as “the flood of lazy, derivative, endlessly recycled outputs from text, image, and avatar models. Like the animal feed it is named for, it is cheap, filling, and nutritionally void. And like animal feed, it is ladled out by the ton. In today’s culture, slop is not a glitch. It is the business plan” (n.p.). In contrast, ‘doom’ is more a reference to the affective consequence of this environment that produces a recursive engagement with negativity, despair, and crisis that sustains itself through the very compulsions the feed induces (Nguyen; Lemenager). While slop names the texture of digital mediation, doom perhaps describes its tone, a sensibility that arises when users are trapped in cycles of passive consumption and anxiety. The two are co-constitutive: slop fuels doom by saturating attention with low-stakes affective noise, while doom gives slop its addictive pull through an anticipatory orientation toward catastrophe (Ytre-Arne and Moe). When combined in a user’s feed, slop and doom produce a range of experiential phenomena. For example, researchers have linked endless scrolling with what is popularly called “brain rot (cognitive decline) and bed rot (sedentary digital overuse)” (Aysi et al. 767). While there is much to be said about the bio-psycho-social effects of Internet use, that is not my framework here. Rather, I situate this discussion in terms of Taina Bucher’s “algorithmic imaginary” and David Langdon’s notion of the “digital gothic” wherein he argues that “the age of anxiety has been brought inward—worry and anxiety has been invited inside, into private, mental spaces” through the Internet (976). I argue that one of the most evident spaces in which this takes place is in the experience of slop and doomscrolling. The fear of rotting away, in either one’s bed or one’s brain, certainly fits the gothic in nature, tone, and style. It should be noted, by way of argument, that the experience of slop and doom content does not discount the many and varied ways connectivity enriches our lives and nourishes our emotional worlds through digital community and connection, which I have discussed extensively elsewhere (Glitsos; Glitsos). While there is a substantial body of scholarship foregrounding the negative psychosocial effects of social media use, such as addiction, distraction, and diminished well-being (see Du et al; Shannon et al.), there is also an emerging stream of research that highlights the capacity for mindful and intentional engagement with digital platforms, even for adolescents (see Boer). Studies have shown that when users approach social media with self-awareness and reflective purpose, it can foster social connection, identity expression, and even psychological resilience (Bayer et al.). This more nuanced literature challenges the deficit model of social media use, suggesting that digital participation can be both self-regulatory and prosocial under conditions of mindful engagement (Shabahang et al.). However, that evidence is not mutually exclusive to the idea that there is also a pervasive sense of being drawn into a bigger, inscrutable entity that shapes contemporary experience in gothic tones, especially in reference to spaces like the Dark Web (Šalamoun), the monstrous digital (Glitsos, Deuze, and Ellingsen), or in the case here, being drawn into an ‘endless scroll’ condition, whereby perfectly defined algorithms born from massive data networks can keep a user scrolling for hours on end, and often in 15-second snippets. I refer here to an exemplary post from an Internet user that sets the tone of this piece and captures the primary experience first-hand. The Reddit user monstr2me writes: The internet makes me miserable for 80% of the time I’m on it, but I just can’t get out. Does anyone else feel like this? Just doomscrolling and sucking in random, often completely useless information for the sake of nothing. ... Have I developed mild to moderate anxiety from constant exposure to news and social media that indicate we’re headed to unavoidable collapse? Sure have. (monstr2me) If, as Mark Deuze wrote, “we live in rather than with media” (Deuze, Life in Media; Media Life), then are we really living in Scroll Land? The ‘Algorithmic Imaginary’ of Scroll Land The endless scroll effect, which is called “infinite scroll” in user interface design terms, was invented by Aza Raskin in 2006 (Knyzelis). This design pattern automatically loads new content as users approach the end of a page, removing natural stopping cues and encouraging prolonged engagement. While Raskin himself later warned of its addictive potential (Rixen et al.), most platforms have not only embedded infinite scroll into their interface, but have also combined this feature with algorithmically curated feeds, where machine learning systems dynamically prioritise and sequence content to maximise attention (Zuboff). The design works in tandem with algorithms that monitor user behaviour in real time, selecting items most likely to elicit further interaction, creating what Taina Bucher calls “the algorithmic imaginary” where users experience an endless, personalised media stream that feeds upon itself. In Bucher’s words, the “algorithmic imaginary” can be understood as the way the “algorithm seizes the social imaginary through the various affective encounters it generates” (39). This definition takes on a darker inflection when coupled with the knowledge that platforms can deliberately manipulate feeds to provoke certain affective encounters. This practice was most starkly revealed in the wildly unethical case of the ‘emotional contagion study’, in which Facebook, in tandem with Cornell University researchers, manipulated the emotional tone of content in the News Feeds of nearly 700,000 users over the course of a week in order to examine how different emotions are ‘contagious’, ultimately “proving that emotional contagion happens also in online environments” (Jouhki et al). So not only does the algorithm produce an imaginary that “become[s] part of ‘force-relations’ and [is] generative of different experiences, moods and sensations” (Bucher 39), but those experiences resonate and travel between users, reminiscent of how Melissa Gregg and Gregory Seigworth define affect as “shuttling intensities” between contacts (1). So how does slop and doom come to dominate a feed? How do we fall down the uncanny rabbit hole in the first place? It can be as quick and easy as clicking on one negative headline, which is common and very easy to do, especially if we want to stay informed on current events, or are simply curious about a topic. However, social media algorithms pick up on that engagement and amplify more emotionally charged content to maximise attention (Milli et al.). In a study by Milli et al., researchers found that, on one platform, the “engagement-based ranking algorithm amplifies emotionally charged, out-group hostile content that users say makes them feel worse about their political out-group” (1). We have likely all felt the flood of these emotions, hostile but also indignant, and even though we are ‘outside’ the political group feeding these emotions we continue to engage with the negativity in a kind of political reflex. It is like being drawn into a story by a provocative character, but the character is actually oneself: a mirror reflection of one’s own emotional dysregulation. An emotional doppelgänger, if you will, anxious and ready to fight shadows. What comes to fruition is our own disturbing resemblance to the main character in Scroll Land, the mirror image, who is now caught in a loop. We stare at the screen, but we are staring at ourselves; ‘through a smartphone, darkly’. Thus, it is oneself that becomes “the central figure of the Gothic, that creepy character who simultaneously draws our gaze and makes us avert our eyes” (Kavka 211), provoking das unheimliche (see Freud), the uncanny, arguably the cradle of the gothic. Positioning this in David Langdon’s framework, this is “the core of the Digital Gothic, where the unnerving reflections of social concerns that mark the form are constructed not merely from the text itself, but from the audience’s own behaviour and response to the form it manifests in” (982). This is to describe a confluence of shadows, the collapsing of oneself with the Scroll, the Other, the Social, and the ‘algorithmic imaginary’. The loop is surreal. The endless supply of cheap-to-produce, AI-generated slop can drown a user’s feed, and it is contaminated with the utterly bizarre. In an article published on NPR, the journalist describes how this kind of content “made Facebook a very bizarre, very creepy place” (Bond). Facebook has always been a strangely liminal space, featuring reruns of old high school friends and long-forgotten memories, sometimes crushing memories, coming back to haunt us (Bucher 38), but when Shrimp Jesus exploded into the mainstream news media (Reddy et al.), it was clear there had been a transition to something more violently weird. The bizarre breaches of slop and doom are exactly what David Langdon would describe as “the Digital Gothic in action” (982). In an article published on Fast Company titled “Facebook’s AI Slop Hellscape Is Already Here”, writer Harry McCracken relates how, “suddenly, [his] feed was crawling with fake elderly, self-pitying cake bakers basking in the love of real Facebook members” (n.p.). These ‘zombie grandparents’ are part of a much larger trend toward what is popularly called the Dead Internet Theory, which asserts that “activity and content on the internet, including social media accounts, are predominantly being created and automated by artificial intelligence agents” (Renzella and Rozova). This state of ‘media life’ is is dominated by chronic viewing of absurd content featuring objects produced by GANs (‘generative adversarial network’, which is a kind of machine learning model that can generate super-realistic images through training on datasets) that look like elderly people who are crying over birthday cake, as well as crustacean-bodied Jesus, and bot-fuelled misinformation, on what we now consider might be a ‘dead thing.’ This condition is nothing if not gothic in ambiance and aesthetic. Fig. 1: This image is part of the Shrimp Jesus meme phenomenon, which gained popularity on Facebook in 2024. (Source: Wikimedia Commons, CC0 1.0 Universal Public Domain Dedication.) When slop and doom dominate our feeds, users flirt with gothic anxiety, and it seeps into their lives. I am not suggesting that we are all living in Scroll Land all the time, but I am suggesting that some users may, at some time in their media life, fall into this space. According to Langdon, in a world where interaction has become a key component of media consumption, the Gothic problematises that interaction, specifically by creating works that mislead, misinform, or distort the truths that the casual consumer of modern media comes to rely upon. (982) For example, in an in-depth study, researchers from Stanford and Georgetown found massive amounts of scam and spam content like “unlabelled AI-generated images” are gaining high volumes of engagement on Facebook but “many users do not seem to recognize that the images are synthetic” (DiResta and Goldstein). Media literacy is challenged by rapidly accelerating technology, and even experienced Internet users may be hard-pressed to quickly judge whether a face or profile is ‘real’ or ‘synthetic’. In fact, a 2022 study evaluating the photorealism of AI-synthesised faces found that these synthesis engines have surpassed the uncanny valley, producing faces that are not only indistinguishable from real ones but are also perceived as more trustworthy (Nightingale and Farid 1). When reviewing the ‘faces’ on a platform such as thispersondoesnotexist.com, a site that generates an artificial human on each visit that is unbelievably realistic, we are met with the knowledge that human faces are no longer the site of authentic human encounter. The breakdown of trust precipitates paranoia, which is a supremely gothic experience. There is something so uncanny about the inability to trust what appears as a ‘human’ face. As slop and doom increasingly work their way into our feeds, and therefore our unconscious, we are met by cognitive dissonances that drive paranoia and anxiety—a human face that has never actually been a human at all, a non-face. Scholars have recently argued that facelessness has taken on new significance in the digital era (Leone). In his chapter exploring Slender Man in Internet folklore, Bruno Surace remarks that “the lost face is a perturbing object as a synecdoche of a dehumanization that coincides with a loss of sociality” (118). Looking someone in the face is a powerful mode of relating to the Other, but one which has been transmogrified and reshaped by digital practices by way of dissolving the trust that the human face has traditionally provided. Putting the examples above all together, there is a sense that in the liminal void of Scroll Land, the identities we encounter are either dead, unreal, or our dark doppelgängers. In these many and diverse ways, the conditions of Bucher’s “algorithmic imaginary” are uncanny (35, 38, 39) and creepy (39), which are key elements of the ‘digital gothic’ experience. On the other side of the equation are the hacking groups and the big tech firms operating on and through these platforms, which are devoted to extracting our data by any means necessary, including by slop and doom. We swim in headlines like: “The True Story of How Your Data Was Stolen to Fix Elections” (Lott-Lavigna), “Cambridge Analytica Is Just the Tip of the Iceberg” (Amnesty International), “Tea App Hack: User Data Stolen from Women's Dating Safety App” (Karnowski), and “Facebook’s Controversial Experiment: Big Tech Is the New Big Pharma” (Boesel). And those are just from the mastheads, not to mention the anxieties bubbling up from the darker corners of the Web that fabulate stories about fantastical digital horrors, like the COVID vaccine being able to connect the human body to Wi-Fi (Nelson). In some ways, it is almost as if paranoia and anxiety form the primary condition of the Scroll Land experience, but these experiences have become diffuse and ill-directed because the source of the anxiety is unclear or ambiguous. Users know they are being mined but cannot feel the drill going in, just the yield to the slippery swipe of the endless scroll, an experiential manifestation of Bauman and Lyon’s “liquid surveillance”, whereby “the condition of being watched and seen has thereby been reclassified from a menace into a temptation” (26). But perhaps in the context of 2025 it is both menace and temptation. In her chapter “Posthuman Interstellar Gothic”, Holly-Gale Millette describes the “millennial gothic mode” as one that is “gripped by anxiety that succeeds from humans who are dominated, shaped and devoured by the built structures of late capitalism” (1198). For Shoshana Zuboff, “in this new world, paranoia and anxiety function as sources of protection from machine invasion for profit” (n.p.), which is perhaps partly why conspiracy and creepypastas become such powerful and viral cultural trends, a bit like the stories of old lore that are mythologised and passed down to ‘ward off the evil spirits’. These are ambivalent experiences in which users are both perturbed and titillated, both menaced and seduced. This Is a Scroll Check Point: Escaping from Scroll Land These experiences have given rise to another phrase in the Internet vernacular: “touching grass”. The phrase implies that users are so drowned in virtual space that they need to remind themselves what is ‘real and natural’ by going ‘outside’ and touching something organic (Horne and Sharpe). Recent scholarship confirms other strategies too, such as Reza Shabahang and René Weber's work on ‘mindful’ and ‘harmonious’ consumption of negative news, in which the authors explain ways to “adopt an agentic mindset toward negative news” by “perceiving their engagement as within their control and sustaining that sense of agency throughout the consumption process” ("How Should We" 5). Finally, there are even ‘scroll checkpoints’ that pop up on user feeds; these ostensibly are short clips from creators to help break up the loop or the doom spiral, but often end up as just more content we wade through with eyes glazed over. With that idea in mind, this is your scroll checkpoint complete. Please, touch grass. References Adami, Marina. “AI-Generated Slop Is Quietly Seizing the Internet: Is It a Threat to Journalism or a Problem That Will Fix Itself?” Reuters Institute for the Study of Journalism, 26 Nov. 2024. . Amnesty International. “‘The Great Hack’: Cambridge Analytica Is Just the Tip of the Iceberg.” 11 Oct. 2021. . Aysi, Alya, et al. "Short-Form Content, Brain Rot, and Bed Rot: A Literature Review of the Impact on University Students." Proceeding of International Conference on Social Science and Humanity, 2 (2025): 767-76. DOI: 10.61796/icossh.v2i3.167. Bauman, Zygmunt, and David Lyon. Liquid Surveillance: A Conversation. Polity, 2013. Bayer, Joseph B., et al. "Social Media Elements, Ecologies, and Effects." Annual Review of Psychology 71 (2020): 471-97. . Boer, Maartje, et al. "Adolescents' Intense and Problematic Social Media Use and Their Well-Being in 29 Countries." Journal of Adolescent Health 66.6 (2020): S89-S99. DOI: 10.1016/j.jadohealth.2020.02.014. Boesel, Whitney Erin. “Facebook’s Controversial Experiment: Big Tech Is the New Big Pharma.” TIME, 3 July 2014. . Bond, Shannon. “AI-Generated Spam Is Starting to Fill Social Media. Here’s Why.” NPR, 14 May 2024. . Bucher, Taina. “The Algorithmic Imaginary: Exploring the Ordinary Affects of Facebook Algorithms.” Information, Communication & Society 20.1 (2017): 30–44. . Deuze, Mark. Life in Media: A Global Introduction to Media Studies. MIT P, 2023. Deuze, Mark. Media Life. Polity, 2012. DiResta, Renée, and Josh A. Goldstein. “How Spammers and Scammers Leverage AI-Generated Images on Facebook for Audience Growth.” Misinformation Review, 15 Aug. 2024. . Du, Mingxuan, et al. "Association between Problematic Social Networking Use and Anxiety Symptoms: A Systematic Review and Meta-Analysis." BMC Psychology 12.1 (2024): 263. DOI: 10.1186/s40359-024-01705-w. Freud, Sigmund. “The ‘Uncanny.’” The Standard Edition of the Complete Psychological Works of Sigmund Freud. Ed. and trans. James Strachey. Vol. 17. Hogarth Press, 1955 [1919]. 217–256. Glitsos, Laura, Steinar Ellingsen, and Mark Deuze. “Nightmare Fuel: Skibidi Toilet and the Monstrous Digital.” M/C Journal 27.6 (2024). . ———. Somatechnics and Popular Music in Digital Contexts. Springer, 2019. ———. Ways of Feeling: The Transformation of Emotional Experience in Music Listening in the Context of Digitisation. PhD diss., 2016. . Gregg, Melissa, and Gregory J. Seigworth, eds. The Affect Theory Reader. Durham, NC: Duke UP, 2010. Horne, George, and Benjamin T. Sharpe. “Esports Are Pretty Far from Bodhi Trees: Touch Grass for Performance and Well-Being.” Journal of Electronic Gaming and Esports (2024). Jouhki, Jukka, Epp Lauk, Maija Penttinen, Niina Sormanen, and Turo Uskali. "Facebook’s Emotional Contagion Experiment as a Challenge to Research Ethics." Media and Communication 4.4 (2016): 75-85. Karnowski, Steve. “Hackers Breach Allianz Life Insurance Company and Expose Personal Data of US Customers.” AP News, 27 July 2025. . Kavka, Misha. “The Gothic on Screen.” The Cambridge Companion to Gothic Fiction. Ed. Jerrold E. Hogle. Cambridge: Cambridge UP, 2006. 209–228. Knyzelis, Milvydas. “The Philosophical Aspect of Contemporary Technology: Ellulian Technique and Infinite Scroll within Social Media.” Filosofija Sociologija 35.1 (2024): 31–9. . Langdon, David. “Anxiety in the Digital Age.” The Palgrave Handbook of Contemporary Gothic. Ed. Catherine Bloom. Cham: Palgrave Macmillan, 2020. 973–984. Lemenager, Stephanie. “Moods of the Feed: Doomscrolling and Affective Saturation.” Environmental Humanities 15.1 (2023): 23–41. Leone, Massimo, ed. The Hybrid Face. New York: Routledge, 2023. Lott-Lavigna, Ruby. “The True Story of How Your Data Was Stolen to Fix Elections.” VICE, 27 July 2024. . McCracken, Harry. “Facebook’s AI Slop Hellscape Is Already Here.” Fast Company, 5 Mar. 2025. . Millette, Holly-Gale. “Posthuman Interstellar Gothic.” In The Palgrave Handbook of Contemporary Gothic. Ed. Catherine Bloom. Cham: Palgrave Macmillan, 2020. 1191–1208. Milli, Smitha. et al. "Engagement, User Satisfaction, and the Amplification of Divisive Content on Social Media." PNAS Nexus 4.3 (2025). DOI: 10.1093/pnasnexus/pgaf062. Mitchell, Sarah. “Doomscrolling Makes You 12 Times More Likely to Suffer Serious Mental Health Issues.” Daily Telegraph, 23 Apr. 2025. . monstr2me. “The Internet Makes Me Miserable for 80% of the Time I’m on It, But I Just Can’t Get Out. Does Anyone Else Feel Like This? ” r/CasualConversation. Reddit, 2021. . Nelson, Felicity. “Can COVID-19 Vaccines Connect Me to the Internet?” Medical Republic, 14 Apr. 2021. . Nightingale, Sophie J., and Hany Farid. "AI-Synthesized Faces Are Indistinguishable from Real Faces and More Trustworthy." Proceedings of the National Academy of Sciences 119.8 (2022): e2120481119. DOI: 10.1073/pnas.2120481119. Nguyen, Ashley. “Doomscrolling: Anxiety, Compulsion, and the Political Economy of Infinite News.” Social Media + Society 7.3 (2021). Read, Max. “The Internet’s AI Slop Problem Is Only Going to Get Worse.” Intelligencer, 25 Sep. 2024. . Reddy, Abhiram, Josh A. Goldstein, and Renee DiResta. “From Shrimp Jesus to Fake Self-Portraits, AI-Generated Images Have Become the Latest Form of Social Media Spam.” The Conversation, 24 Apr. 2024. . Renzella, Jake, and Vlada Rozova. “The ‘Dead Internet Theory’ Makes Eerie Claims About an AI-Run Web. The Truth Is More Sinister.” The Conversation, 20 May 2024. . Rixen, Jan Ole, et al. "The Loop and Reasons to Break It: Investigating Infinite Scrolling Behaviour in Social Media Applications and Reasons to Stop." Proc. ACM Hum.-Comput. Interact. 7 (2023): article 228. DOI: 10.1145/3604275. Šalamoun, Jiří. "Monstrous Technology in Thomas Pynchon’s Bleeding Edge: The Internet as Terror and Transformation." Critique: Studies in Contemporary Fiction 65.4 (2024): 776-85. DOI: 10.1080/00111619.2023.2242765. Shabahang, Reza, et al. “Doomscrolling Evokes Existential Anxiety and Fosters Pessimism about Human Nature: Evidence from Iran and the United States.” Computers in Human Behavior Reports 2.3 (2024): 1–10. Shabahang, Reza, and René Weber. “How Should We Approach Negative News in the Media? A 'Mindful' and 'Harmonious' Consumption of Negative News by Users Might Be an Answer.” Frontiers in Psychology 16 (2025). DOI: 10.3389/fpsyg.2025.1606604 Shabahang, Reza, Emma F. Thomas, Karen M. Douglas, René Weber, Joël Billieux, Marc Eric Santos Reyes, Ho Phi Huynh, Zsolt Demetrovics, and Ágnes Zsila. “Mindful Use of Social Media Is Associated with Weaker Conspiracy Beliefs—Evidence from the Philippines, Australia, and Iran.” SSRN (2025). . Shannon, Holly, et al. "Problematic Social Media Use in Adolescents and Young Adults: Systematic Review and Meta-Analysis." JMIR Ment Health 9.4 (2022): e33450. DOI: 10.2196/33450. Surace, Bruno. “Featureless Faces: A Film Aesthetics.” In The Hybrid Face. Ed. Massimo Leone. New York: Routledge, 2023. 109–128. Ytre-Arne, Brita, and Hallvard Moe. “Doomscrolling, Information Overload, and Media Fatigue: Theorizing News Consumption in Times of Crisis.” Journalism Studies 22.13 (2021): 1739–55. Zuboff, Shoshana. The Age of Surveillance Capitalism: The Fight for a Human Future at the New Frontier of Power. New York: PublicAffairs, 2019.